A guide to company taxation in Nigeria : Federal Republic of Nigeria - Federal Board of Inland Revenue; Federal Board of Inland Revenue (Lagos : Federal Board of Inland Revenue, 1972)
This is a guide to company taxation in Nigeria published by the Federal Board of Inland Revenue in 1972.
lje 4/3/19
Arch
Keywords: Taxation; Company taxation; Nigeria